2018
DOI: 10.1016/j.bios.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Determination of microcystin-LR, employing aptasensors

Abstract: Cyanobacteria produce toxins such as microcystin-LR (MC-LR), which are associated with potential hepatotoxicity in humans. The detection of cyanobacteria and their toxins in drinking water and sea food is therefore crucial. To date, methods such as high performance liquid chromatography (HPLC), protein phosphatase inhibition assay (PPIA), and Raman spectroscopy have been employed to monitor MC-LR levels. Although these techniques are precise and sensitive, they require expensive instrumentation, well-trained p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 93 publications
0
15
0
Order By: Relevance
“…Aptasensors are biosensors that employ aptamer as recognition element. In developing aptasensors, nanomaterials that are regarded as potential agents are mostly considered because of their physico-chemical properties including small size, disposability and high surface area [ 158 ]. Various highly specific and sensitive aptasensors-based optical (such as colorimetric, fluorescent, SERS, Electrochemiluminescence (ECL) aptasensors) and electrochemical-based aptasensors currently exist for the determination of MC-LR [ 158 , 159 , 160 ].…”
Section: Biosensor Methods To Detect Microcystinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aptasensors are biosensors that employ aptamer as recognition element. In developing aptasensors, nanomaterials that are regarded as potential agents are mostly considered because of their physico-chemical properties including small size, disposability and high surface area [ 158 ]. Various highly specific and sensitive aptasensors-based optical (such as colorimetric, fluorescent, SERS, Electrochemiluminescence (ECL) aptasensors) and electrochemical-based aptasensors currently exist for the determination of MC-LR [ 158 , 159 , 160 ].…”
Section: Biosensor Methods To Detect Microcystinsmentioning
confidence: 99%
“…In developing aptasensors, nanomaterials that are regarded as potential agents are mostly considered because of their physico-chemical properties including small size, disposability and high surface area [ 158 ]. Various highly specific and sensitive aptasensors-based optical (such as colorimetric, fluorescent, SERS, Electrochemiluminescence (ECL) aptasensors) and electrochemical-based aptasensors currently exist for the determination of MC-LR [ 158 , 159 , 160 ]. A novel aptasensor based on SERS where MC-LR aptamer and its corresponding complementary DNA fragments (cDNA) were conjugated to gold nanoparticles (AuNPs) and magnetic nanoparticles (MNPs), respectively, used as signal and capture probes (aptamer-AuNPs and cDNA-MNPs conjugates) was constructed and applied for highly sensitive MC-LR detection.…”
Section: Biosensor Methods To Detect Microcystinsmentioning
confidence: 99%
“…Aptasensors based on the recognition of aptamer and target has been explored and widely applied in bioanalysis because of its fast response time, good specicity and selectivity. Up to now, combining with different signal readouts, various aptasensors were developed including electrochemical, 6 uorescent, 7 colorimetric, 8 electrochemiluminescence 9 and surface enhanced Raman scattering (SERS) etc., which have displayed a good future in the detection of small molecules, proteins and drugs, etc. Among these aptasensors, uorescent aptasensors have attracted special attention because their excellent features such as high sensitivity, high efficiency and simple operation etc.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, microcystin-LR (MC-LR), produced by cyanobacteria, is one of the most toxic. Because of their sensitivity and relative simplicity, aptasensing strategies have received great attention for the detection of MC-LR [91]. Gan et al reported a multiple amplified enzyme-free biosensor for MC-LR detection using G-quadruplex/hemin functionalized mesoporous silica with redox-active intercalators [92].…”
Section: Toxinsmentioning
confidence: 99%